Immunoluminometric assay for copeptin measurement in cerebrospinal fluid: technical aspects and pilot study - Mindt, Sonani; Andrade-Barazarte, H.; Tokhi, Ursala; Ludtka, C.; Neumaier, Michael; Hänggi, Daniel (Clinica chimica acta, 2019)
Background - Copeptin acts as surrogate marker under stress stimuli, as well as an outcome predictor based on serum or plasma concentration in patients suffering intracranial hemorrhage, aneurysmal subarachnoid hemorrhage (aSAH), and stroke. The aim of this study was to establish a method for quantification of copeptin levels in cerebrospinal fluid (CSF) and to demonstrate its clinical applicability in patients following aSAH. - Methods - This assay was validated for CSF samples using a commercial immunoluminometric assay (IMLA). For the control group (10 patients), CSF copeptin levels were determined in patients without signs of acute neurological diseases and who underwent a diagnostic lumbar puncture. The pilot cohort included calculation of copeptin levels in CSF and in serum of patients following aSAH. - Results - The control group had CSF copeptin levels lower than 0.78pmol/L−1. Among patients with aSAH, CSF copeptin values had a mean of 20.1pmol/L−1 and serum copeptin concentrations had a mean of 61.39pmol/L−1. - Conclusions - This assay provides to best of our knowledge for the first time initial ranges values of CSF copeptin for patients without acute neurological disease and in patients with aSAH. Thus, it opens new doors to develop further calculations and relationships between diseases biomarker and outcome prediction.